Ovarian malignant mixed Müllerian tumor: a rare case report from Tanzania. Issue 10 (20th October 2020) - Pallangyo, Angela; Pyuza, Jeremia J; Andongolile, Alice A; Mbwambo, Daniel; Claver, Jackson P; Koosa, Ummil-Khairat; Lema, Kennedy; Amsi, Patrick; Nkya, Gilbert; Mremi, Alex
Abstract: Malignant mixed Müllerian tumor of the ovary is rare aggressive tumor that is histologically defined by the presence of malignant epithelial and stromal components. We report a 37-year-old woman who consulted our facility complaining of abdominal distention and a painful palpable mass over her lower abdomen. Physical examination including computerized tomography revealed a complex cystic mass lesion on the left ovary with extensive omental involvement. Ovarian cancer was suspected and the patient underwent debulking surgery. The histopathology of the specimen revealed a high-grade tumor composed of both malignant epithelial and sarcomatous elements. Both epithelial and stromal components stained positive for p53 immunostaining. Before the initiation of chemotherapy, on 5th day postoperation, the patient was found unresponsive. The stage of the disease seems to be the most important prognostic factor, thus emphasis should be made to identify it in earlier stages.